Ecological Stoichiometry of Bumblebee Castes, Sexes, and Age Groups - Krams, Ronalds; Munkevics, Māris; Popovs, Sergejs; Dobkeviča, Linda; Willow, Jonathan; Contreras Garduño, Jorge; Krama, Tatjana; Krams, Indrikis A. (Frontiers in Physiology, 2021)
Ecological stoichiometry is important for revealing how the composition of chemical elements of organisms is influenced by their physiological functions and ecology. In this study, we investigated the elemental body composition of queens, workers and males of the bumblebee Bombus terrestris, an important pollinator throughout Eurasia, North America and northern Africa. Our results showed that body elemental content differs among B. terrestris castes. Young queens and workers had higher body nitrogen concentration than ovipositing queens and males, while castes did not differ significantly in their body carbon concentration. Furthermore, the carbon-to-nitrogen ratio was higher in ovipositing queens and males. We suggest that high body nitrogen concentration and low carbon-to-nitrogen ratio in young queens and workers may be related to their greater amount of flight muscles and flight activities than to their lower stress levels. To disentangle possible effects of stress in the agricultural landscape, further studies are needed to compare the elemental content of bumblebee bodies between natural habitats and areas of high-intensity agriculture.